TINJAUAN HUKUM PENERTIBAN IZIN UKL DAN UPL DI KOTA SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 - Arif Wicaksono (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTBasic Law of Control of UKL and UPL License under Law No. 32 of 2009 on Environmental Protection and Management. Previously many changes. However, nowadays, the existing law is Law Number 32 Year 2009 is very detailed as follows: (a) Aspects of planning carried out through the inventory of the environment, the determination of ecoregion areas and the preparation of RPPLH (Environmental Management Plan for Protection). (B) Aspects of Natural Resources Utilization made under the RPPLH. But in this Law it is regulated that if an area has not yet developed RPPLH then the utilization of Natural Resources shall be implemented based on the carrying capacity and environmental capacity. (C) Controlling aspects of pollution and damage  to environmental functions including prevention, mitigation and recovery. (D) The incorporation of new control instruments, including: KLHS, Spatial Planning, Criteria for Environmental Damage, AMDAL, UKL-UPL, Licensing, Other Instruments in accordance with the needs and / or development of Science. (E) Conservation of the environment through conservation of Natural Resources, Natural Resources Reserve, and / or the preservation of atmospheric functions. (F) Monitoring and enforcement aspects. There is a strict regulation mandated in Law Number 32 Year 2009, namely the imposition of criminal and civil sanctions related to violations of AMDAL. The articles governing the sanctions are: (a) Sanctions against persons conducting business / activities without environmental permits; (B) Sanctions against persons preparing EIA documents without having a competency certificate; (C) Sanctions against officials granting environmental permits without the EIA or UKL-UPL document.Keywords : License Control, Amdal, UKL-UPL